Sustainable Retail Development New Success Strategies - Yudelson, Jerry; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
"Sustainable Retail Development" addresses the emerging issue of green retail buildings and retail development that will grow significantly in importance over the next half-decade, a trend seen throughout the developed world. This volume is a practical and comprehensive guide to greening retail real estate, including green building and marketing strategies, corporate sustainability programs and features a 10-point "action program" for greening any retail real estate portfolio. "Sustainable Retail Development" should be essential reading for professionals in design, construction and operations of shopping centers and retail stores. Well illustrated, this volume features over 30 green retail developments from North America, Europe, South America, Asia and Australia, as well as interviews with 25 leading industry experts. Leading green building expert Jerry Yudelson presents a solid business case for greening retail real estate and shows how leading companies are advancing sustainable retail businesses.
Sustainability Matters -- Green Buildings Around the World -- What Is a Green Building? -- The Business Case for Green Retail -- Costs of Greening Buildings and Developments -- Solar Power -- Greening Shopping Centers -- Greening Retail Buildings -- Greening Retail Interiors -- Operating Green Retail Spaces -- Marketing Sustainable Retail Development -- Sustainable Retail Organizations -- The Ten-Point Program for Retail Sustainability.
Keywords: Geography; Regional planning; Architecture; Engineering design; Building construction; Environmental sciences; Economics; Geography; Landscape/Regional and Urban Planning; Environment, general; Business/Management Science, general; Building Types and Functions; Building Construction, HVAC, Refrigeration; Engineering Design